2009
DOI: 10.2208/kaigan.65.1016
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Large-Scale Flood on Water Quality of Tokyo Bay

Abstract: To clarify influences of large-scale floods on water quality of Tokyo Bay, we performed field measurements on pollutant loads under flood conditions, evaluated the long-term trends of SS, organic materials, and nutrient fluxes, and investigated its relation with DO and nutrients in Tokyo Bay. The large flood event caused by the attack of typhoon no. 0709 was observed to have significantly huge environmental impacts on Tokyo Bay. The comparison between the pollutant loads and DO in Tokyo Bay indicates that subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The monitoring data have been made public in annual reports for FY1971-97 by Chiba (Chiba Prefectural Government Environmental Department 1972-1998), for FY1971-2018by Tokyo (Tokyo Metropolitan Government Bureau of Environmental Protection 1972-2019 and for FY1971-2008 by Kanagawa (Kanagawa Prefectural Government Environmental Department 1972-2009. The data also began to be provided via the Internet from FY1990 by Chiba (Chiba Prefectural Government 2020) and Tokyo (Tokyo Metropolitan Government Bureau of Environmental Protection 2020), and from FY2001 by Kanagawa (Kanagawa Prefectural Government 2020).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring data have been made public in annual reports for FY1971-97 by Chiba (Chiba Prefectural Government Environmental Department 1972-1998), for FY1971-2018by Tokyo (Tokyo Metropolitan Government Bureau of Environmental Protection 1972-2019 and for FY1971-2008 by Kanagawa (Kanagawa Prefectural Government Environmental Department 1972-2009. The data also began to be provided via the Internet from FY1990 by Chiba (Chiba Prefectural Government 2020) and Tokyo (Tokyo Metropolitan Government Bureau of Environmental Protection 2020), and from FY2001 by Kanagawa (Kanagawa Prefectural Government 2020).…”
Section: Datamentioning
confidence: 99%
“…At the head of Tokyo Bay, the effect of south winds in summer on the hypoxia has been reported (Suzuki et al 2012;Suzuki 2013). A study of the influences of large-scale floods on the water quality of Tokyo Bay has revealed that large amounts of organic matter transported by large floods can cause the development of hypoxia at the head of the bay (Nihei et al 2009).…”
Section: Other Factors Affecting Hypoxiamentioning
confidence: 99%